Developmental trajectories of the socioeconomic status of occupational aspirations during adolescence - Miyamoto, Ai [Verfasser]; Wicht, Alexandra [Verfasser] (My University, 2020)
“Prominent theories of career development suggest age-related changes in adolescents' occupational aspirations. However, little is known about how exactly and to what extent, adolescents' aspirations change, particularly regarding the socioeconomic status (SES) of aspired occupations. We aim at extending our knowledge of the developmental trajectories of the SES of occupational aspirations and potential gender differences in those trajectories. We used longitudinal data from the German National Educational Panel Study (NEPS) consisting of a large and representative sample of secondary school students (N = 5,964, 50% females) from Grades 8 to 10 (age 14–16). Data were collected via a paper and pencil survey which was carried out in classrooms. Our analysis of a latent growth curve model revealed that adolescents experienced small increases in the SES of occupational aspirations from Grades 8 to 10. Multi-group models reveal that females initially aspired to higher-SES occupations and their aspirations exhibited larger growth over time compared to males. Our findings are in line with those from other countries but not with all, indicating some cross-cultural variabilities. Within cultures, the developmental trajectories of the SES of occupational aspirations seem to be similar across age-cohorts in the last 30 years. Despite women aspire to higher-SES occupations during adolescence, they often obtain lower-SES occupations than men in adulthood. Future research is needed to better understand the link between gender differences in the SES of occupational aspirations in adolescence and gender differences in the SES of occupational attainment in adulthood.” (authors’ abstract; BIBB-Doku)
Keywords: P 1.1 Jugendliche; L 5 Beratung & Orientierung; G 1.3.2 Bildungsverhalten und -verläufe; 370; 300; Jugendlicher; Berufswunsch; Bildungsaspirationen; sozioökonomischer Status; Geschlechterdifferenz; Nationales Bildungspanel